Digital lingual appliance combined with micro-screws for the treatment of a skeletal bimaxillary protrusion and 'gummy' smile - Chen Yu Hua; Gao Yuan; He Jiao Jiao; Fu Shan Min; Wang Lei (Sciendo, 2023)
This case report describes the lingual orthodontic treatment of a 28-year-old female patient who presented with a bimaxillary protrusion malocclusion, a hyperdivergent facial pattern, mentalis strain, and a 'gummy' smile. To achieve favourable occlusal and facial results, the four first premolars were extracted, and micro-screws utilised to provide maximum anchorage. With the widespread application of three-dimensional technology, a digital goal-oriented treatment plan was applied for its predictability and precision. A fully customised lingual appliance system with preset torque in the anterior teeth combined with ribbon-wise arch wires was placed to prevent excessive lingual inclination of the incisors during retraction. As a result, an attractive facial profile and a well-aligned dentition with ideal intercuspation was obtained.